2008
DOI: 10.1007/s00467-008-0900-4
|View full text |Cite
|
Sign up to set email alerts
|

Calcimimetics in CKD—results from recent clinical studies

Abstract: Secondary hyperparathyroidism (sHPT) is a frequent complication in patients with chronic kidney disease (CKD) and a known contributor to the development of vascular calcification and renal osteodystrophy (CKD-BMD). Secondary hyperparathyroidism is also related to increased cardiovascular mortality in CKD patients. With the discovery that molecules can modulate the calciumsensing receptor (CaR) of the parathyroid gland, new treatment options are now available to control sHPT. Calcimimetics activate the CaR and-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
(40 reference statements)
0
6
0
1
Order By: Relevance
“…In secondary HPT, hypocalcaemia and phosphate retention stimulate the parathyroid glands, resulting in parathyroid hyperplasia and increased PTH concentrations. Secondary HPT is one of the first metabolic complications of chronic kidney disease (CKD) and has been associated with untoward effects such as renal bone disease, increased cardiovascular morbidity and death from (cardio)vascular calcifications. Successful kidney transplantation can reverse secondary HPT.…”
Section: Introductionmentioning
confidence: 99%
“…In secondary HPT, hypocalcaemia and phosphate retention stimulate the parathyroid glands, resulting in parathyroid hyperplasia and increased PTH concentrations. Secondary HPT is one of the first metabolic complications of chronic kidney disease (CKD) and has been associated with untoward effects such as renal bone disease, increased cardiovascular morbidity and death from (cardio)vascular calcifications. Successful kidney transplantation can reverse secondary HPT.…”
Section: Introductionmentioning
confidence: 99%
“…Several different authors proposed proof showing that control of the calcium intake or lowering parathyroid hormone levels, in particular with the help of calcimimetic cinacalcet, results in a reduction in calcium content in the vasculature of individuals with end-stage renal disease. Eventually, this did not result in a decrease in atherosclerotic cardiovascular disease in patients with end-stage renal disease [ 81 ].…”
Section: Pathophysiologic Considerations Of Ascvd In Ckdmentioning
confidence: 99%
“…It is found that secondary hyperparathyroidism frequently develops during stages 3 and 4 of CKD. 7 Treatment options aimed at suppressing iPTH currently include dietary P restrictions, P binding, and supplementation with active Vit D and Ca. Dialysis provides additional means of P removal as well as helping to control acid–base balance and removes uremic toxins detrimental to bone health.…”
Section: Introductionmentioning
confidence: 99%
“… 18 Cinacalcet shifts the set point for Ca-regulated iPTH secretion to the left leading to a reduction in iPTH secretion. 7 …”
Section: Introductionmentioning
confidence: 99%